Dynamics and deformability of α-, 310- and π-helices - Narwani, Tarun Jairaj; Craveur, Pierrick; Shinada, Nicolas K; Santuz, Hubert; Rebehmed, Joseph; Etchebest, Catherine; de Brevern, Alexandre G. (Archives of Biological Sciences, 2018)
Protein structures are often represented as seen in crystals as (i) rigid macromolecules (ii) with helices, sheets and coils. However, both definitions are partial because (i) proteins are highly dynamic macromolecules and (ii) the description of protein structures could be more precise. With regard to these two points, we analyzed and quantified the stability of helices by considering α-helices as well as 310- and π-helices. Molecular dynamic (MD) simulations were performed on a large set of 169 representative protein domains. The local protein conformations were followed during each simulation and analyzed. The classical flexibility index (B-factor) was confronted with the MD root mean square flexibility (RMSF) index. Helical regions were classified according to their level of helicity from high to none. For the first time, a precise quantification showed the percentage of rigid and flexible helices that underlie unexpected behaviors. Only 76.4% of the residues associated with α-helices retain the conformation, while this tendency drops to 40.5% for 310-helices and is never observed for π-helices. α-helix residues that do not remain as an α-helix have a higher tendency to assume β-turn conformations than 310- or π-helices. The 310-helices that switch to the α-helix conformation have a higher B-factor and RMSF values than the average 310-helix but are associated with a lower accessibility. Rare π-helices assume a β-turn, bend and coil conformations, but not α- or 310-helices. The view on π-helices drastically changes with the new DSSP (Dictionary of Secondary Structure of Proteins) assignment approach, leading to behavior similar to 310-helices, thus underlining the importance of secondary structure assignment methods. https://doi.org/10.2298/ABS170215022N This article was presented on the Belgrade Bioinformatics Conference 2016 (BelBI2016) [http://belbi2016.matf.bg.ac.rs/] Received: February 15, 2017; Revised: May 2, 2017; Accepted: May 30, 2017; Published online: June 23, 23017 How to cite this article: Narwani TJ, Craveur P, Shinada NK, Santuz H, Rebehmed J, Etchebest C, de Brevern AG. Dynamics and deformability of α-, 310- and π-helices. Arch Biol Sci. 2018;70(1):21-31.